Multifactorial Model of Glycemic Control: Socio-Demographic, Dietary, and Behavioral Determinants among Patients with Type 2 Diabetes – A Cross-Sectional Study - Rabie, Hadeer Badin; Ahmed, Jabbar Taresh; Ali, Wasen Abdul Ameer; Altemimi, Mahmood Thamer (American Journal of Biomedicine and Pharmacy, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a major public health issue influenced by factors beyond medication. Dietary habits, lifestyle behaviors, and socio-demographic characteristics have shown significant impacts on glycemic control. However, integrated models examining these factors collectively remain limited. This study aims to evaluate the combined influence of these variables among T2DM patients. Objective: This study aims to evaluate the combined influence of these variables among T2DM patients. Methodology: This cross-sectional study included 250 patients with Type 2 Diabetes. The data was gathered through in-person interviews with patients through questionnaires distributed on the basis of axes. Result: The mean of age 53.3±9.8 (with range; 32-75) years while the mean of BMI is 30.98±5.88 (with a range of 18.55-52.79).The results of the study reveal that for more than half of patients, their duration of disease with T2DM was 1-5 years (50.8%),The high percentage (76.8%) of the patients with T2DM have any first-degree relatives with diabetes. A very high percentage (86.4%) of the patients with T2DM have high levels of HbA1c. The mean of HbA1c was 8.97±2.237 (with a range of 5.7-14.9).The study results of demonstrated that most patients suffering from diabetes (67.6%) practiced light physical activity, such as slow walking and light housework.A very high percentage (99.6%) of diabetics eat three meals a day. 54.8% of patients suffering from diabetes eat snacks and sugary pastries between meals.Also,the findings of this study indicate that 82.0% of patients follow unhealthy food patterns. Finally, the results found there were negative correlations between HbA1c and the overall food pattern scores (-0.713). Conclusion: The study results show a statistically significant relationship between Socio-demographic, dietary habits and lifestyle behaviors variables and the incidence and control on the type 2 diabetes mellitus (T2DM).